Pengaruh ekuitas merek dan word of mouth terhadap keputusan pembelian skateboard padaright wing store di samarinda - Dedy Ismaida; Tetra Hidayati; Mohamad Wasil (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
Dedy Ismaida ‘’The Influence of brand equity and word of mouth on the decision of purchasing skateboard at right wing store in samarinda’’ brand equity in this research consists of the brand awreness, perceived quality, product quality, brand trust, brand loyalty. And word of mouth consist of the talkers, topics, tools, taking part, tracking. Also knowing which dominant variable on the decision of purchasing            This research Program using Multiple Linear Regression Analysis tool  SPSS version 22.0 The research populations is consumer at Right Wing Store in Samarinda. At same time was used for this Research is a much as 65 respondents with in non probability technique sampling and the accindental sampling method, the questionnaires as for collecting datas specifically.            The Research results indicate that brand equity and word of mouth  significant is positive reacted effect to decision of purchasing other thing that word of mouth is be come to be dominant variable which affecting on the decision of purchasing